MOTIVATION OF ELEMENTARY LEVEL STUDENTS OF “ENGLISH FOR ADULTS” PROGRAM IN LEARNING ENGLISH AT LBPP LIA MALANG - RAHMAWATI, HANIFA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Rahmawati, Hanifa. 2014.  Motivation  of  Elementary Level Students of “English for Adults”  Program in Learning English  at  LBPP LIA Malang. Study Program of English, Faculty of Cultural Studies, Universitas  Brawijaya. Supervisor: Fatimah; Co-supervisor: Yana Shanti Manipuspika.   Keywords:  second  language,  motivation,  elementary  level, English for Adults Program, LBPP LIA Malang.    There are some factors influencing the learners’ success in second language learning. One of them is motivation. Motivation in second language learning is defined as the learner’s orientation with regard to the goal of learning a second language.  This study  discusses about  motivation  of  Elementary Level students of  “English for Adults”  Program in learning English at  LBPP LIA Malang. The study was conducted in order to  find out the primary  type of motivation and the most dominant motivation in learning English. This study used quantitative approach. The instrument used was AMTB questionnaire, proposed by Gardner in 1985. The motivation part of the questionnaire consists of eight items divided into two parts: four items for instrumental motivation and other four for integrative motivation. The participants of the study were 36 students, which were divided into 4 levels. Therefore, the participants were 9 students of each level which were taken randomly. The result revealed  that  the primary  type of motivation of each level was instrumental motivation.  The students of each level have  different  dominant motivation in learning English. Elementary Level 1 students are learning English for their future career, in order to make them become knowledgeable people, and for getting a good job. Elementary Level 2 students are learning English in order to make them become more knowledgeable people and for getting a  good job. Elementary  Level  3 students are learning English  for their future career and  in order to make them become  more knowledgeable people.  Elementary Level  4 students are learning English for their future career and for getting a good job.    In conclusion, the students of each elementary level have the same primary type of motivation and different dominant motivation in learning English. The writer suggests the institute to make a better program for their students. It is suggested for future researchers to use another instrument in collecting data in order to prove whether the other instruments are applicable in other research. The writer also suggests Study Program of English to add more references related with motivation.